Lowered Fasting Blood Glucose (FBG) in a Prediabetic Individual with HIV Despite Struggle with Weight Control Management- CASE STUDY (FS17-06-19). (13th June 2019) - Perez, Alicia Sneij; Seminario, Leslie; Tamargo, Javier; Martinez, Sabrina; Campa, Adriana; Huffman, Fatma; Trepka, Mary Jo; George, Florence; Baum, Marianna
Abstract: Objectives: HIV infection has previously been associated with malnutrition and wasting; however, with the initiation of antiretroviral therapy (ART), a growing number of people living with HIV (PLWH) are becoming centrally obese, with disproportionate weight accumulation around the abdominal area and fat losses in the rest of their body (periphery face, arms and legs), indicative of lipodystrophy. As a result, some PLWH may struggle simultaneously with central fat accumulation and peripheral losses, trying to balance these 2 opposite effects. Methods: PB is a 62-year-old, African-American male infected with HIV for 12 years, receiving an NRTI regimen. Participating in the Miami Adult Studies in HIV (MASH) Cohort, PB started a 6-month nutrition intervention targeted to lower diabetes risk in prediabetic PLWH. Baseline body mass index (BMI) was 24.1 kg/m 2 and waist circumference (WC) was 36.5 inches. Despite having the initial intention to lose weight, PB gained ∼12.4 lbs just a month after initiation. When questioned about the weight gain, PB revealed that he had started taking an appetite stimulant ( Megace ) to address the wasting on his periphery, claiming that he looked "sickly". PB stopped taking Megace after he gained >20 lbs (12.3% Wt∆) in 4 months. BMI at this time was 26.3 kg/m 2 and WC was 45.5 inches, reflecting a substantially increased risk for metabolic complications. With WC increasing 9 inches and hip circumference increasing only 2 inches, it is evident that a considerable amount of the weight accumulation occurred around the waist. As can be seen, he among others in his situation, are struggling with conflicting goals by simultaneously trying to reduce central obesity and prevent peripheral losses and wasting, something that may be unique to PLWH. Results: Despite the participant's difficulties in weight management, his fasting blood glucose (FBG) improved after the 6-month nutrition intervention, with a −14 mg/dL improvement, lowering associated risk for diabetes and cardiometabolic complications. Conclusions: This improvement in FBG levels suggests that despite the difficulty of effective weight management in these patients, proper glucose values may still be achieved with nutrition counseling and education, thus lowering risk for diabetes and associated complications. Funding Sources: NIGMS-RISE funding, National Institute on Drug Abuse 5U01DA040381-03 and FIU-Dissertation Funding.